The Role of Multimodal Prehabilitation in Improving Postoperative Functional Outcomes in Colorectal Cancer Patients: A Review - Rayhan Shafithri; Zati Hasyyati Ali; Willa Mutia Syafrida (Journal of Food, Nutrition, and Health Advances, 2026)
Colorectal cancer is the third most common type of cancer worldwide and the second leading cause of death. Surgery remains the primary treatment modality, but the resulting surgical stress often triggers significant metabolic, cardiovascular, and psychological responses. Post-surgery, patients are at risk of a 20% to 40% decrease in functional capacity, leading to an increased risk of complications and prolonged hospital stay. This review aims to evaluate the benefits of a multimodal pre-rehabilitation program on improving post-operative functional and clinical outcomes in colorectal cancer patients. The methods of this article were searched through Scopus and PubMed databases for the period 2021-2026. Keywords used in the literature search included "prehabilitation" or "pre-habilitation," "colorectal cancer," and "functional outcome" or "6MWT." The results show that a multimodal pre-rehabilitation program integrating physical exercise, nutritional support, and psychological support (anxiety management and relaxation techniques) yields positive outcomes. The key efficacy parameter, 6MWT, demonstrated a highly significant increase in distance traveled compared to the control group, both pre-operatively (+96 meters) and at the 4- to 8-week post-operative evaluation. Furthermore, this intervention plays a role in reducing the incidence of major complications (Clavien-Dindo grade ≥ III) and has been shown in numerous studies to shorten hospital stays. The conclusion is that multimodal pre-rehabilitation is an effective perioperative preparation approach for colorectal cancer patients. This program consistently improves functional capacity, accelerates post-operative recovery, reduces the risk of serious complications, and shortens hospital stays, making it a standard strategy for improving patients' quality of life.